Serum level of antibody against benzo[a]pyrene-7,8-diol-9,10-epoxide-DNA adducts in people dermally exposed to PAHs - Borska, Lenka; Andrys, Ctirad; Krejsek, Jan; Palicka, Vladimir; Chmelarova, Marcela; Hamakova, Kvetoslava; Kremlacek, Jan; Borsky, Pavel; Fiala, Zdenek (Journal of immunology research, 2014)
Some specific antibodies indicate the presence of antigenic structures on DNA (DNA adducts) that can play an important role in the process of mutagenesis and/or carcinogenesis. They indicate the presence of increased genotoxic potential (hazard) prior to the formation of disease (primary prevention). The present study was focused on the serum level of benzo[a]pyrene 7,8-diol-9,10-epoxide-DNA adducts antibodies (anti-BPDE-DNA) in psoriatic patients (n = 55) dermally exposed to different levels of polycyclic aromatic hydrocarbons (PAHs). The general goal of the study was to contribute to better understanding of the value of the assumed biomarker (anti-BPDE-DNA) for evaluation of the organism's answer to genotoxic exposure to PAHs. Elevated level of exposure to PAHs resulted in the increased level of anti-BPDE-DNA. However, almost all levels of anti-BPDE-DNA ranged within the field of low values. Both variants of GT (CCT-3% and CCT-5%) induced higher expression of anti-BPDE-DNA in the group of nonsmokers. Significant relations between the level of anti-BPDE-DNA and PASI score, total duration of the therapy, or time of UVR exposure were not found. Further studies are needed to reduce interpretation uncertainty of this promising bioindicator.
Keywords: adukty DNA; protilátky; Male; biologické markery; Middle Aged; psoriáza; Biomarkers; Adolescent; Ultraviolet Therapy; dehet uhelný; Adult; Aged; dospělí; mužské pohlaví; senioři; kůže; 7,8-Dihydro-7,8-dihydroxybenzo(a)pyrene 9,10-oxide; Smoking; polycyklické aromatické uhlovodíky; mladiství; terapie ultrafialovými paprsky; Antibodies; lidé; Psoriasis; ženské pohlaví; Skin; Humans; 7,8-dihydro-7,8-dihydroxybenzo(a)pyren 9,10-oxid; DNA Adducts; Female; lidé středního věku; kouření; Polycyclic Aromatic Hydrocarbons; Coal Tar